Rancang Bangun Tong Sampah Cerdas Menggunakan Suara Sebagai Media Informasi Berbasis Arduino Uno - Siti Nur Asia; Sofyan Sofyan; Husna Saleh; Muhammad Ikhwan Mardin; M Noor Fuad (Universitas Darul Ulum, 2025)
Garbage is one of the problems that we often encounter in the community. One of the factors causing the accumulation of garbage is the lack of public awareness to dispose of garbage in its place. In this problem, it is necessary to have a smart trash can using sound information media which includes Ultrasonic Sensors as distance detectors and trash volume detectors, Servos are used to control the trash can cover, Speakers are used as information media, DFPlayer mini is used as a voice recorder and microcontrollers are used as input data processors from the components used. The trash can cover will open and close automatically by detecting humans at a distance of ≤ 30 cm then detecting the height of the trash from the trash can cover ≤ 10 cm then the trash can is full then the trash can cover will not open and emit information in the form of sound. The method used in this study is the experimental method, namely by designing, assembling, and testing a smart trash can system based on Arduino Uno. Testing was conducted to evaluate the performance of the sensor, and the voice module in responding to the presence of objects in front of the trash can. This research is useful for the community because it can increase awareness in disposing of garbage in its place through an interactive approach in the form of sound, thus supporting the creation of a cleaner and more orderly environment. In addition, scientifically, this research contributes to the development of science and technology, especially in the field of hardware that can be used as a basis for similar innovations in various fields of life.